2018
DOI: 10.1002/lno.10959
|View full text |Cite
|
Sign up to set email alerts
|

High‐turbidity events in Western Lake Erie during ice‐free cycles: Contributions of river‐loaded vs. resuspended sediments

Abstract: High‐turbidity events (HTEs) are common phenomena in shallow‐water environments that can alter ecological interactions. The relative contributions of river input (external loading) vs. resuspension (internal loading) to the occurrence, duration, and influenced areas of HTEs are not fully understood in most systems, owing to the lack of long‐term, source‐specified sediment maps. Using a Finite Volume Community Ocean Model‐based wave‐current forced sediment model, we investigated sediment dynamics in the shallow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 60 publications
(114 reference statements)
2
49
0
Order By: Relevance
“…S3), suggesting a minor contribution of river discharge to the sediment plume visible in the MODIS imagery. This is consistent with (Sydor ) who found that the principle sources of turbidity in the western arm are wave driven coastal erosion of clay banks and resuspension, and similar to findings of Niu et al (), who found the contribution of resuspension to the size of high‐turbidity areas in western Lake Erie exceeded the contribution from river loading.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…S3), suggesting a minor contribution of river discharge to the sediment plume visible in the MODIS imagery. This is consistent with (Sydor ) who found that the principle sources of turbidity in the western arm are wave driven coastal erosion of clay banks and resuspension, and similar to findings of Niu et al (), who found the contribution of resuspension to the size of high‐turbidity areas in western Lake Erie exceeded the contribution from river loading.…”
Section: Resultssupporting
confidence: 92%
“…Pollutants from urban watersheds discharged in stormwater plumes can threaten sensitive coastal ecosystems and water sources (Lahet and Stramski ; Petus et al ). In contrast, internal loading processes including coastal erosion and resuspension contribute to turbidity in wind‐driven plumes (Lee et al ; Niu et al ) and their size is a function of the wind forcing as well as basin morphology relative to wind direction (Schwab et al ). Their impact on coastal ecosystems is a function of their size as well as ambient nearshore water quality and character of the eroded/resuspended sediment (Eadie et al ).…”
mentioning
confidence: 99%
“…This criterion was satisfied in most of the regions over the MCBs during Hurricane Irene (2011) and a similar system in the East Frisian Wadden Sea under storm conditions (Grashorn et al, 2015). Given that Mao and Xia (2017) and Niu and Xia (2017) successfully applied the 3D radiation stress-based (Mellor, 2005) FVCOM/SWAVE to the Great Lakes (note: Niu et al, 2018applied Mellor, 2015, this study extended the application of this model to the MCBs and their paired inlets. In addition, modeled results from the updated 3D radiation stress formulation of Mellor (2015) were compared with the 2D version in Section 4.3.…”
Section: Descriptions Of the Modeling Systemmentioning
confidence: 84%
“…Seasonally, predominant wind direction changes across the basin, which can influence the amount of mixing within the basin. Northeastern winds are mainly in the spring, whereas southwestern winds dominate in the fall (Niu et al, 2018). Winds during the summer bloom months are weak and vary in direction, allowing for bloom proliferation.…”
Section: Study Sitementioning
confidence: 99%
“…WLE is typically more turbid in the fall due to waves caused by winds and river discharge (Niu et al, 2018), which is likely the cause of a shift in main water type. Large early bloom season (June) surface plume areas were likely residual spring discharge combined with strong northerly winds, which dominate in the spring (Niu et al, 2018). Late season (October) surface areas were influenced by an increase in fall storms and runoff.…”
Section: Spatial and Temporal Variability Of The Detroit Rivermentioning
confidence: 99%